랜선 투어의 콘텐츠 특성이 지역 이미지, 관광지불의도 및 장기체류의도에 미치는 영향 - 성예슬(Yae Seul Sung), 백주아(Joo A Baek) (융합관광콘텐츠연구, 2025)
목적 본 연구는 랜선 투어의 콘텐츠 특성이 관광지에 대한 인지적 이미지와 정서적 이미지 형성에 어떻게 영향을 미치며, 이러한 이미지가 소비자의 관광지불의도와 장기체류의도에 어떠한 영향을 미치는지를 실증적으로 분석하였다. 최근 유튜브나 TV프로그램 등의 플랫폼을 통해 목적지를 간접적으로 경험해보는 가상 여행 콘텐츠가 확산됨에 따라, 이를 지역 관광 활성화를 위한 마케팅 도구로 활용하려는 학문적 관심이 높아지고 있는 상황이다. 본 연구는 이러한 흐름에 주목하여 랜선 투어의 콘텐측 특성이 지역 경제 활성화에 기여할 수 있는지에 대해 초점을 맞추었다. 방법 랜선 투어(가상여행) 콘텐츠를 시청한 경험이 있는 개인을 대상으로 설문조사를 진행하였으며, 총 180부의 유효 응답을 수집하였다. 수집된 데이터를 SPSS 23.0과 AMOS 26.0을 활용하여 빈도분석, 신뢰도 분석, 탐색적 요인분석, 구조방정식모형(SEM)을 분석하였다. 결과 랜선 투어 콘텐츠 특성 4가지 오락성, 신뢰성, 정보성, 간접체험성 모두 관광지의 인지적 이미지와 정서적 이미지에 긍정적인 영향을 미치는 것으로 나타났다. 또한, 이러한 지역 이미지는 시청자의 관광지불의도와 장기체류의도에도 각각 유의미한 영향을 주는 것으로 나타났다. 결론 본 연구는 랜선 투어의 콘텐츠 특성이 소비자의 관광 관련 행동 즉, 지불의사와 장기체류 의사에 영향을 미친다는 결과는 가상 경험을 통해 형성된 이미지가 실제 방문의도 또는 경제적 가치에 영향을 줄 수 있음을 시사하며, 지역 경제 활성화를 위한 관광 콘텐츠 개발 방향에 중요한 시사점을 제공한다. Purpose This study empirically analyzed how the LAN tour content characteristics influence the formation of cognitive and emotional destination images, and how these images affect consumers' willingness to pay in tourism and long-term stay intention. With the recent spread of virtual travel content that allows indirect experiences of destinations through platforms such as YouTube and TV programs, academic interest in utilizing this content as a marketing tool for regional tourism activation has increased. This study focused on whether the content characteristics of LAN tours can contribute to local economic revitalization. Methods A survey was conducted targeting individuals who have experience watching LAN tour (virtual travel) content, collecting a total of 180 valid responses. The collected data were analyzed using SPSS23.0 and AMOS26.0 for frequency analysis, reliability analysis, exploratory factor analysis, and structural equation modeling(SEM). Results All four LAN tour content characteristics-entertainment, credibility, informativeness, and indirect experience-were found to positively influence both the cognitive and emotional destination images. Furthermore, these destination images had significant effects on viewers’ willingness to pay in tourism and long-term stay intention. Conclusion This study suggests the potential of LAN tour content characteristics by demonstrating their influence on consumer tourism-related behaviors, namely willingness to pay and long-term stay intention. It implies that images formed through virtual experiences can impact actual visit intentions or economic value, providing important implications for the development of tourism content aimed at revitalizing local economies. KCI Citation Count: 0